Comparative changes in sugars and lipids show evidence of a critical node for regeneration in safflower seeds during aging - Zhou, Lanyu; Lu, Lijie; Chen, Chao; Zhou, Tao; Wu, Qinghua; Wen, Feiyan; Chen, Jiang; Pritchard, Hugh W.; Peng, Cheng; Pei, Jin; Yan, Jie (Frontiers in Plant Science, 2022)
Seeds have the critical node (CN) where vigor drops sharply during storage. Exploring the specific locations of CN in different species of plants is crucial for understanding the biological storage properties of seeds and refining seed lifespan management. Safflower, a bulk oil crop that relies on seeds for propagation, has a short seed life. However, at present, its biological characteristics during storage, especially the metabolic changes of substances and cell structures, are not clear, which restricts the refined management of safflower seed life and its effective preservation in gene banks. Here, we report the seed survival curve of oilseed safflower under the controlled deterioration treatment, found that the seed germination showed an inverted S shape, and the germination rate in the first 12 days of aging was above 86%. It shows that the vicinity of C10 was the CN for the reduction of vigor, and the seeds in the “plateau” interval had different germination speeds at the same imbibition time. Further analysis of the changes in sugar concentration found that the sucrose content decreased slowly with aging. The content of raffinose and two monosaccharides decreased abruptly at C10, which was similar to the germination curve. Differentially metabolized lipids, namely lysophospholipids (LPC, LPE) and PMeOH up-regulated at C3. The fatty acid content began to accumulate at C6, and the content of phospholipids (PC, PE, PI) and glycolipids (DGDG, MGDG and SQDG) decreased significantly from C10. In addition, the activities of raffinose hydrolase α-GAL and glyoxylate key enzyme ICL decreased with aging in safflower seeds. Subsequently, confocal and transmission electron microscopy can also reveal the shrinkage of the seed plasma membrane at C10 and the late fragmentation. Seedling phenotypic indicators and TTC activity assays also verified the CN. To sum up, C10 is a key node of seed aging. Before the node, sugar and lipid metabolism, especially fatty acid metabolism into sugar, can make up for the energy consumed by aging. After this, the seeds were irreversibly damaged and their viability was greatly reduced. The root cause of this behavior was that the cell structure at the node began to be destroyed.